HUBUNGAN BERAT BADAN LAHIR DAN FREKUENSI PEMERIKSAAN ANC DENGAN KEJADIAN STUNTING PADA ANAK UMUR 0-59 BULAN - lina fiitriani; hilki ofan (J-KESMAS: Jurnal Kesehatan Masyarakat, 2021)
The problem of stunting (stunting) is one of the nutritional problems faced in the world, especially in poor and developing countries. This study aims to determine the relationship between age and parity with the incidence of stunting in children aged 0-59 months. The research design used was analytical survey method with a cross sectional research approach. The population in this study were all children aged 0-59 months. The number of samples was 67 children. The results showed that there was a relationship between age and the incidence of stunting in children aged 0-59 months with a value of 0.000 (<0.05). While the results ofthe research on the relationship between parity and the incidence of stunting in children aged 0-59 months, the value was 0.002 (<0.05), which means that there is a relationship between parity and the incidence of stunting in children aged 0-59 months.